Gracilis Anatomic Anterolateral Ligament Reconstruction: Technical Note - Gabriele Thiebat, M.D.; Lorenzo Maria Maggioni, M.D.; Roberto De Pamphilis, M.D.; Claudio Manzini, M.D.; Andrea Panzeri, M.D.; Marco Pungitore, M.D. (Arthroscopy Techniques)
Anterior cruciate ligament reconstruction alone may not adequately address rotational stability in cases with combined anterior cruciate ligament and anterolateral ligament (ALL) injury. The gracilis anatomic anterolateral ligament (GrAAL) reconstruction technique offers an approach that aims to restore rotational stability by anatomically reconstructing the ALL using the gracilis tendon autograft while preserving its native tibial insertion. This procedure requires only a single femoral fixation point, making it a cost-effective and less invasive alternative to other anatomic ALL reconstruction techniques. This technical note outlines the surgical methodology and potential advantages of our approach.